Oxidative Stress Mediates Microcystin-LR-Induced Endoplasmic Reticulum Stress and Autophagy in KK-1 Cells and C57BL/6 Mice Ovaries - Liu, Haohao; Zhang, Xiaofeng; Zhang, Shenshen; Huang, Hui; Wu, Jinxia; Wang, Yueqin; Yuan, Le; Liu, Chuanrui; Zeng, Xin; Cheng, Xuemin; Zhuang, Donggang; Zhang, Huizhen (Frontiers in Physiology, 2018)
Microcystin-leucine arginine (MC-LR) is a cyclic heptapeptide intracellular toxin released by cyanobacteria that exhibits strong reproductive toxicity. However, little is known about its biotoxicity to the female reproductive system. The present study investigates unexplored molecular pathways by which oxidative stress acts on MC-LR-induced endoplasmic reticulum stress (ERs) and autophagy. In the present study, immortalized murine ovarian granular cells (KK-1 cells) were exposed to 8.5, 17 and 34 µg/mL (IC50) of MC-LR with or without N-acetyl-l-cysteine (NAC, 10 mM) for 24 hours, and C57BL/6 mice were treated with 12.5, 25.0 and 40.0 µg/kg•bw of MC-LR with or without NAC (200 mg/kg•bw) for 14 days. The results revealed that MC-LR could induce cells apoptosis and morphologic changes in ovarian tissues, induce oxidative stress by stimulating the generation of reactive oxygen species (ROS), destroying antioxidant capacity, and subsequently trigger ERs and autophagy by inducing the hyper-expression of ATG12, ATG5, ATG16, EIF2α (phosphorylated at S51), CHOP, XBP1, GRP78, Beclin1, and PERK (Thr980). Furthermore, NAC pretreatment partly inhibited MC-LR-induced ERs and autophagy via the PERK/ATG12 and XBP1/Beclin1 pathways. These results suggest that oxidative stress mediated MC-LR-induced ERs and autophagy in KK-1 cells and C57BL/6 mice ovaries. Therefore, oxidative stress plays an important role in female toxicity induced by MC-LR.